Pemanfaatan Strategi Pemasaran Melalui Media Sosial Untuk Meningkatkan Penjualan Produk MAN Sampang - Septian Eko Haryansyah; Moh. Aminullah; Robius Shoffi; Siti Maisaroh (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
This community service is entitled "Utilization of Marketing Strategies Through Social Media to Increase Product Sales". Based on this community service program, it is implemented to increase students' interest in entrepreneurship, develop skills in building a business and utilize digital marketing through social media. This activity is shown to 100 students of MAN Sampang. There are several stages in the implementationof this service, including preparation, implementation, mentoring and training, evaluation and reporting. At the preparation stage, a meeting was held with the school regarding the identification of problems and objectives of the activity, as well as the time of implementation. At the implementation stage, an entrepreneurship seminar was held with the theme Utilization of Marketing Strategies Through SocialMedia to Increase Product Sales. The use of social media in product sales is an interesting topic of discussion among students and academics along with the emergence of start-up businesses and startup businesses. This community service provides benefits for both partners or service participants and for the servants, including: (1) increased knowledge related to generation Z, namely students, increasing sales through social media; (2) after participating in the training, participants expressed a high level of satisfaction with the implementation (3) the servants received several suggestions for further service themes from the audience participants.